A Survey on SmartPhone Honeypot - Ahmed, Dr.Hanaa Mohsin; Hassan, Dr. Nidaa Flaih; A. Fahad, Assmaa (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Smartphones are becomingÂ Â  a dominant form of mobile computing in the world. The Smartphone, as a platform, blends a traditional general computing platform with a specialized mobile phone platform. The general computing tradition is historically open, allowing its owners to install whatever software they choose and to add or remove hardware as they please. Also they are a vault for large amount of personal information about banking, social network, and inter-personal communication. These capabilities and information value make it an attractive target to internet miscreants. This paper presents a survey on recent researches in Smartphone honeypot. Physical and virtual honeypots have been studied in details; however, there is only little work in the field of mobile related honeypot. The survey presents the challenges while setting up a smartphone honeypot, and summarizes the researches published in this area. We clarify the methods used to build their honeypot, and the results they obtained and their recommendations.